„Amicitia quae desinere potest vera nunquam fuit” . Przyjaźń w Listach św. Hieronima ze Strydonu - Kieling, Michał (Vox Patrum, 2020)
The aim of the article is to present friendship on the basis of letters written by St. Jerome of Stridon. In epistolary literature of this Doctor of the Church, it is impossible to find any systematic teaching about friendship. Nevertheless, St. Jerome’s correspondence presents him as a man who maintained relationships with many people and addressed different issues in his letters. The presented article is divided into three parts. The first one concentrates on the subject of exchanging and writing letters, which is a form of befriending people and cherishing such relations. Thanks to those letters the absent person becomes present and the correspondence itself turns into a spiritual conversation. The second part presents people who are Jerome’s friends in his letters. Most of them are associated with the monastic environment (Rufinus of Aquileia, St. Chromatius, Bonozus, Heliodor, Pammachius, Paulinus, Oceanus, Jovinus, Eusebius). The third part is devoted to the story of friendship between St. Jerome and Rufus of Aquileia. They were faithful friends in their youth, but due to the conflict regarding Origen, they finally became enemies. Jerome finds true friendship in Christ, enduring and faithful, that never ceases to exist.